A micro-nano size magnesium-doped indium-coated lithium-rich manganese-based positive electrode material and its precursor and preparation method

By adopting micro-nano-size magnesium-doped indium coating technology on lithium-rich manganese-based positive electrode materials, combined phase doping magnesium, interfacial indium and particle nano-normalization strategies, the problem of poor body phase-interface dynamic characteristics of lithium-rich manganese-based positive electrode materials is solved, and its electrochemical performance is significantly improved.

CN119349666BActive Publication Date: 2025-03-21BEIJING HUAIROU BEIKE NEW ENERGY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411899461.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-21
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

Lithium-rich manganese-based positive electrode materials have problems such as poor body-interface dynamic characteristics and poor structural stability, resulting in a degradation of electrochemical performance.

Method used

The coupling modification method of micro-nano-size magnesium-doped indium coated lithium-rich manganese-based positive electrode material is adopted to jointly improve the structural stability and kinetic performance of the material through bulk-phase doping, interfacial indium and particle nanoification strategies.

Benefits of technology

The electrochemical properties of lithium-rich manganese-based positive electrode materials are significantly improved, the bulk phase-interface dynamic characteristics and structural stability are improved, and the lithium ion mass transfer path is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349666B_ABST
    Figure CN119349666B_ABST
Patent Text Reader

Abstract

The present invention relates to a micro-nano size magnesium-doped indium-coated lithium-rich manganese-based positive electrode material and its precursor and preparation method, belonging to the field of battery technology. The technical problems of poor bulk-interface kinetic characteristics and poor bulk-interface structural stability of lithium-rich manganese-based positive electrode materials in the prior art are solved. The preparation method of the positive electrode material of the present invention first prepares a lithium-rich manganese-based positive electrode material precursor under an inert atmosphere using a transition metal salt solution containing a manganese salt, a precipitant solution, and a complexing agent solution as raw materials, and then mixes the lithium-rich manganese-based positive electrode material precursor, lithium salt and magnesium source evenly, sintering, and obtaining a bulk-doped magnesium micro-nano lithium-rich manganese-based positive electrode material; finally, mixes evenly with an indium source, heats and keeps warm in an oxygen-containing atmosphere, and obtains a lithium-rich manganese-based positive electrode material. The preparation method synergistically improves the structural stability and kinetic performance of the lithium-rich manganese-based positive electrode material from different scales of bulk-interface-particles, and significantly improves its electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a micro-nano-sized magnesium-doped indium-coated lithium-rich manganese-based positive electrode material and a precursor and a preparation method thereof. Background Art

[0002] With the growing demand for battery life in the consumer market, it is imperative to develop new high-energy-density lithium-ion batteries, and the positive electrode material is one of the key factors restricting the energy density of lithium-ion batteries.

[0003] Compared with traditional positive electrode materials such as lithium iron phosphate, ternary nickel cobalt manganese oxide, lithium cobalt oxide and lithium manganese oxide, lithium-rich manganese-based positive electrode materials have higher gram capacity (>250mAh / g), which can significantly improve the energy density of the battery, thereby meeting the needs of electric vehicles and energy storage systems for high endurance, and are an ideal choice for future lithium-ion batteries.

[0004] However, there are still some problems in the commercialization of lithium-rich manganese-based cathode materials. Although the special cation-anion synergistic reaction mechanism provides high capacity, the anion reaction mechanism also leads to problems such as low first efficiency, poor kinetic performance and voltage variation (voltage decay and voltage hysteresis); at the same time, the higher operating voltage is also prone to side reactions between lithium-rich manganese-based cathode materials and electrolytes, which in turn triggers the collapse of the material interface to the bulk structure, resulting in a continuous decline in the electrochemical properties of lithium-rich manganese-based cathode materials.

[0005] To solve these problems, researchers have conducted a lot of research. Patent CN113299902A provides a magnesium-doped modification method to prepare a secondary spherical lithium-rich manganese-based positive electrode material with a gradient distribution of magnesium elements. Although the structural stability of the magnesium-rich region of the secondary spherical particles has been effectively enhanced, the problem of uneven internal stress distribution in the magnesium-poor region of the bulk core has not been improved in a targeted manner. Patent CN118335959A provides a modification method for constructing an inert coating on a lithium-rich manganese-based spherical positive electrode material. By reducing the dissolution of transition metals and introducing oxygen vacancies, the oxygen release, capacity and voltage attenuation problems are suppressed, but the primary particle bulk-interface is not improved in a targeted manner. Patent CN118255402A provides a method for preparing a submicron small-particle lithium-rich manganese-based precursor and its positive electrode material. By adjusting the surface energy of the particles during spray pyrolysis, the growth process of the crystal nucleus is controlled, thereby obtaining submicron-level small-particle lithium-rich manganese precursor spherical particles, which improves the kinetic properties of lithium-rich manganese-based positive electrode materials, but the yield and tap compaction are low.

[0006] In summary, a single strategy such as doping modification, coating modification, and morphology design is difficult to simultaneously solve the many problems existing in lithium-rich manganese-based positive electrode materials. Summary of the invention

[0007] The purpose of the present invention is to solve the technical problems of poor bulk-interface kinetic characteristics and poor bulk-interface structural stability of lithium-rich manganese-based positive electrode materials in the prior art, and to provide a micro-nano-sized magnesium-doped indium-coated lithium-rich manganese-based positive electrode material and its precursor and preparation method. The positive electrode material couples three modification methods of doping-coating-morphology design, and synergistically improves the structural stability and kinetic properties of the lithium-rich manganese-based positive electrode material from different scales of bulk-interface-particles, thereby significantly improving its electrochemical performance.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows.

[0009] In a first aspect, the present invention provides a method for preparing a lithium-rich manganese-based positive electrode material precursor, comprising the following steps:

[0010] Under an inert atmosphere, a transition metal salt solution, a precipitant solution and a complexing agent solution are added to a reactor containing a base liquid. After the addition is completed, the obtained mother liquor is aged for more than 0 hours, filtered, washed and dried to obtain a lithium-rich manganese-based positive electrode material precursor, wherein the transition metal salt includes a manganese salt.

[0011] Preferably, the inert atmosphere is nitrogen, argon or a combination of both.

[0012] Preferably, the manganese salt is a combination of one or more of manganese nitrate, manganese sulfate and manganese acetate.

[0013] Preferably, the transition metal salt further comprises one or a combination of two of a nickel salt and a cobalt salt;

[0014] More preferably, the nickel salt is a combination of one or more of nickel nitrate, nickel sulfate, and nickel acetate; the cobalt salt is a combination of one or more of cobalt nitrate, cobalt sulfate, and cobalt acetate;

[0015] More preferably, in the transition metal salt solution, the total concentration of the transition metal salt is 0.5-4M, and the molar ratio of manganese, nickel and cobalt is x:y:z, 1 / 3≤x<1, 0≤y≤1 / 2, 0≤z≤1 / 2.

[0016] Preferably, the precipitant is a combination of one or more of sodium hydroxide, sodium bicarbonate, sodium carbonate and oxalic acid, and the concentration of the precipitant solution is 0.5-10M.

[0017] Preferably, the complexing agent is a combination of one or more of ammonia water, ammonium sulfate and ammonium chloride, and the concentration of the complexing agent solution is 0.1-5M.

[0018] Preferably, the base liquid is a combination of one or more of deionized water and complexing agent solution, and the pH value of the base liquid is 10.3-12.0.

[0019] Preferably, the precipitant solution and the complexing agent solution are fed separately or in combination.

[0020] Preferably, during the liquid feeding process, the pH value of the solution system in the reactor is maintained at 10.3-12.0, the temperature in the reactor is maintained at 20-80° C., and the stirring speed in the reactor is maintained at 500-2000 r / min.

[0021] Preferably, the aging time is greater than 0 and less than or equal to 48 hours.

[0022] In a second aspect, the present invention also provides a lithium-rich manganese-based positive electrode material precursor prepared by the above preparation method, the chemical formula of which is Mn x Ni y Co z (OH)2, 1 / 3≤x<1, 0≤y≤1 / 2, 0≤z≤1 / 2;

[0023] The average particle size of the lithium-rich manganese-based positive electrode material precursor is 100nm-1μm.

[0024] The morphology of the lithium-rich manganese-based positive electrode material precursor is flaky primary particles.

[0025] In a third aspect, the present invention also provides a method for preparing a micro-nano size magnesium-doped indium-coated lithium-rich manganese-based positive electrode material, comprising the following steps:

[0026] Firstly, a lithium-rich manganese-based cathode material precursor, a lithium salt and a magnesium source are uniformly mixed and sintered to obtain a bulk magnesium-doped micro-nano lithium-rich manganese-based cathode material;

[0027] Then the obtained bulk magnesium-doped micro-nano lithium-rich manganese-based positive electrode material is evenly mixed with an indium source, and heated and kept warm in an oxygen-containing atmosphere to obtain a micro-nano size magnesium-doped indium-coated lithium-rich manganese-based positive electrode material.

[0028] Preferably, the lithium salt is a mixture of one or more of lithium hydroxide, lithium nitrate, lithium carbonate, lithium oxalate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium dioxalatoborate; the ratio of the molar amount of lithium in the lithium source to the total molar amount of the transition metal in the lithium-rich manganese-based positive electrode material precursor is 1.12:0.8-1.25:0.8.

[0029] Preferably, the magnesium source is a mixture of one or more of magnesium nitrate, magnesium oxide, magnesium sulfate, magnesium citrate, magnesium chloride and magnesium lactate.

[0030] Preferably, the molar amount of magnesium in the magnesium source is 0.01%-5% of the total molar amount of transition metals in the lithium-rich manganese-based positive electrode material precursor. More preferably, the molar amount of magnesium in the magnesium source is 0.02%-5% of the total molar amount of transition metals in the lithium-rich manganese-based positive electrode material precursor.

[0031] Preferably, the sintering temperature is 800-900° C., and the sintering time is 10-24 hours.

[0032] Preferably, the indium source is indium nitrate, indium chloride or a mixture of the two.

[0033] Preferably, the molar amount of indium in the indium source is 0.01%-5% of the total molar amount of the transition metal in the lithium-rich manganese-based positive electrode material precursor, and more preferably, the molar amount of indium in the indium source is 0.02%-5% of the total molar amount of the transition metal in the lithium-rich manganese-based positive electrode material precursor.

[0034] Preferably, the bulk magnesium-doped micro-nano lithium-rich manganese-based positive electrode material is uniformly mixed with the indium source by dry mixing or wet mixing or both.

[0035] Preferably, the oxygen-containing atmosphere is one or both of oxygen and air.

[0036] Preferably, the heating and insulation temperature is 300-700°C, and the heating and insulation time is 30min-6h.

[0037] In a fourth aspect, the present invention also provides a micro-nano size magnesium-doped indium-coated lithium-rich manganese-based positive electrode material prepared by the above preparation method.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] The micro-nano size magnesium-doped indium-coated lithium-rich manganese-based positive electrode material of the present invention is coupled with a variety of modification methods. Through bulk magnesium doping, interface indium coating and particle nano-sizing strategies, the lithium ion mass transfer path is synergistically reduced, the bulk-interface kinetic characteristics of the lithium-rich manganese-based positive electrode material are improved, and the bulk-interface structural stability of the lithium-rich manganese-based positive electrode material is maintained, thereby ultimately improving its electrochemical performance.

[0040] Among them, bulk magnesium doping not only expands the (003) crystal plane interlayer spacing and reduces the lithium ion mass transfer resistance, but also improves the bulk structural stability.

[0041] After indium coating, the surface of the positive electrode material can not only form an indium oxide protective layer to inhibit the reaction with the electrolyte, but also introduce stable oxygen vacancies to improve the initial efficiency and capacity. In addition, part of the indium reacts with the residual lithium on the surface to form a lithium indium oxide fast ion conductor, remove the residual alkali on the surface and improve the kinetic performance of lithium ions at the interface.

[0042] In addition, the micro-nano particle size also reduces the mass transfer path of lithium ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0044] Figure 1 In the figure, (a) is the precursor Mn in Comparative Sample 1, Comparative Sample 2 and Example 1. 4 / 6 Ni 1 / 6 Co 1 / 6 (a) is the morphology of the positive electrode material in Example 1.

[0045] Figure 2 The first charge and discharge performance of 2032 half-cells assembled with the positive electrode materials prepared from Comparative Sample 1, Comparative Sample 2 and Example 2 of the present invention.

[0046] Figure 3 The cyclic electrical performance of 2032 half-cells assembled with the positive electrode materials prepared from comparative sample 1 and example 3 of the present invention. DETAILED DESCRIPTION

[0047] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below in conjunction with embodiments.

[0048] In the following examples, various processes and methods not described in detail are conventional methods known in the art. Unless otherwise specified, the materials, reagents, devices, instruments, equipment, etc. used in the following examples can be obtained from commercial sources.

[0049] Comparison sample 1

[0050] (1) First, MnSO4·H2O, NiSO4·6H2O and CoSO4·7H2O were dissolved in deionized water at a molar ratio of Mn:Ni:Co=4:1:1 to prepare a transition metal salt solution with a concentration of 2.0 mol / L. Then, the precipitant NaOH and the complexing agent NH3·H2O were dissolved in deionized water to prepare a precipitant-complexing agent mixed solution with a NaOH concentration of 2.0 mol / L and an NH3·H2O concentration of 0.4 mol / L. Finally, 200 mL of deionized water was added to the reactor and kept warm to 50°C. Nitrogen was pre-flowed as a protective gas, and then the transition metal salt solution and the precipitant-complexing agent mixed solution were simultaneously pumped into the coprecipitation reactor. The stirring speed was set to 1500 rpm and the pH value was controlled at 10.8. After the liquid was added, the mother liquor was aged for 24 hours, then filtered, washed and dried at 120°C for 24 hours to obtain the precursor Mn 4 / 6 Ni 1 / 6 Co1 / 6 (OH)2, its morphology is Figure 1 As shown in (a), from Figure 1 As can be seen in (a), comparative sample 1 prepared a monolithic precursor with a particle size of 200 nm.

[0051] (2) The precursor prepared in step (1) (the transition metal ion in the precursor is denoted as TM) and lithium carbonate (Li:TM=1.2:0.8) powder are mixed evenly by dry mixing, and then kept at 850°C for 15 hours to obtain a positive electrode material with a particle size of about 200 nm. The 2032 half-cell is assembled for testing. The first discharge performance is as follows: Figure 2 As shown, the electrical performance after 500 cycles at 1C rate is as follows Figure 3 shown.

[0052] Comparison sample 2

[0053] (1) First, MnSO4·H2O, NiSO4·6H2O and CoSO4·7H2O were dissolved in deionized water at a molar ratio of Mn:Ni:Co=4:1:1 to prepare a transition metal salt solution with a concentration of 2.0 mol / L. Then, the precipitant NaOH and the complexing agent NH3·H2O were dissolved in deionized water to prepare a precipitant-complexing agent mixed solution with a NaOH concentration of 2.0 mol / L and an NH3·H2O concentration of 0.4 mol / L. Finally, 200 mL of deionized water was added to the reactor and kept warm to 50°C. Nitrogen was pre-flowed as a protective gas, and then the transition metal salt solution and the precipitant-complexing agent mixed solution were simultaneously pumped into the coprecipitation reactor, the stirring speed was set to 1500 rpm, the pH value was controlled at 10.8, and the liquid feeding was completed. The obtained mother liquor was first aged for 24 hours, then filtered, washed and dried at 120°C for 24 hours to obtain the precursor Mn 4 / 6 Ni 1 / 6 Co 1 / 6 (OH)2, its morphology is Figure 1 As shown in (a), from Figure 1 As can be seen in (a), comparative sample 2 prepared a monolithic precursor with a particle size of 200 nm.

[0054] (2) The precursor prepared in step (1) was mixed evenly with lithium carbonate (Li:TM=1.2:0.8) and magnesium oxide (TM:Mg=1.00:0.01) powders by dry mixing, and then kept at 850°C for 15 hours to obtain a magnesium-doped modified positive electrode material with a particle size of about 200 nm. It was assembled into a 2032 half-cell for testing. The first discharge performance was as follows: Figure 2 shown.

[0055] Example 1

[0056] (1) First, MnSO4·H2O, NiSO4·6H2O and CoSO4·7H2O were dissolved in deionized water at a molar ratio of Mn:Ni:Co=4:1:1 to prepare a transition metal salt solution with a concentration of 1.5 mol / L. Then, the precipitant NaOH and the complexing agent NH3·H2O were dissolved in deionized water to prepare a precipitant-complexing agent mixed solution with a NaOH concentration of 4.0 mol / L and an NH3·H2O concentration of 1.0 mol / L. Finally, 200 mL was added to the reactor and kept warm to 50°C. Nitrogen was pre-flowed as a protective gas, and then the transition metal salt solution and the precipitant-complexing agent mixed solution were simultaneously pumped into the coprecipitation reactor. The stirring speed was set to 1500 rpm, and the pH value was controlled at 10.9. After the liquid was added, the obtained mother liquor was aged for 24 hours, then filtered, washed and dried at 120°C for 24 hours to obtain the precursor Mn 4 / 6 Ni 1 / 6 Co 1 / 6 (OH)2, its morphology is Figure 1 As shown, from Figure 1 As can be seen in (a), a monolithic precursor with a particle size of 200 nm was prepared.

[0057] (2) The precursor prepared in step (1) is mixed with lithium carbonate (Li:TM=1.15:0.8) and magnesium oxide (TM:Mg=1.00:0.02) powders by dry mixing, and then kept at 850°C for 15 hours to obtain a magnesium-doped modified positive electrode material with a particle size of about 200 nm; the magnesium-doped modified positive electrode material is further mixed with In(NO3)3 (TM:In=1.00:0.01) by wet mixing, heated and stirred until it becomes a paste, and then dried, and then ground and kept at 600°C in an air atmosphere for 5 hours to obtain a micro-nano-sized magnesium-doped indium-coated lithium-rich manganese-based positive electrode material with a particle size of about 200 nm, and the morphology is as follows: Figure 1 As shown in (b).

[0058] Example 2

[0059] (1) First, MnSO4·H2O, NiSO4·6H2O and CoSO4·7H2O were dissolved in deionized water at a molar ratio of Mn:Ni:Co=4:1:1 to prepare a transition metal salt solution with a concentration of 2.0 mol / L. Then, the precipitant NaOH and the complexing agent NH3·H2O were dissolved in deionized water to prepare a precipitant-complexing agent mixed solution with a NaOH concentration of 2.0 mol / L and an NH3·H2O concentration of 0.4 mol / L. Finally, 200 mL of deionized water was added to the reactor and kept warm to 50°C. Nitrogen was pre-flowed as a protective gas, and then the transition metal salt solution and the precipitant-complexing agent mixed solution were simultaneously pumped into the coprecipitation reactor, the stirring speed was set to 1500 rpm, the pH value was controlled at 10.8, and the liquid feeding was completed. The obtained mother liquor was first aged for 24 hours, then filtered, washed and dried at 120°C for 24 hours to obtain the precursor Mn 4 / 6 Ni 1 / 6 Co 1 / 6 (OH)2 powder.

[0060] (2) The precursor prepared in step (1) is mixed evenly with lithium carbonate (Li:TM=1.2:0.8) and magnesium oxide (TM:Mg=1.00:0.01) powders by dry mixing, and then kept at 850°C for 15 hours to obtain a magnesium-doped modified positive electrode material with a particle size of about 200 nm; the magnesium-doped modified positive electrode material is further mixed evenly with In(NO3)3 (TM:In=1.00:0.005) by wet mixing, heated and stirred until it becomes a paste, and then dried, and then ground and kept at 600°C in an air atmosphere for 5 hours to obtain a micro-nano-sized magnesium-doped indium-coated lithium-rich manganese-based positive electrode material with a particle size of about 200 nm. The micro-nano-sized magnesium-doped indium-coated lithium-rich manganese-based positive electrode material is assembled into a 2032 half-cell for testing. Figure 2 As shown, the first cycle discharge capacity is 294.9 mAh / g and the first efficiency is 88.56%.

[0061] Example 3

[0062] (1) First, MnSO4·H2O, NiSO4·6H2O and CoSO4·7H2O were dissolved in deionized water at a molar ratio of Mn:Ni:Co=4.5:0.5:1 to prepare a transition metal salt solution with a concentration of 2.0 mol / L. Then, the precipitant NaOH and the complexing agent NH3·H2O were dissolved in deionized water to prepare a precipitant-complexing agent mixed solution with a NaOH concentration of 3.0 mol / L and an NH3·H2O concentration of 0.4 mol / L. Finally, 200 mL of deionized water was added to the reactor and kept warm to 40°C. Nitrogen was pre-flowed as a protective gas, and then the transition metal salt solution and the precipitant-complexing agent mixed solution were simultaneously pumped into the coprecipitation reactor, the stirring speed was set to 1000 rpm, the pH value was controlled at 11.2, and the liquid feeding was completed. The obtained mother liquor was first aged for 24 hours, then filtered, washed and dried at 120°C for 24 hours to obtain the precursor Mn 3 / 4 Ni 1 / 12 Co 1 / 6 (OH)2 powder.

[0063] (2) The precursor prepared in step (1) and lithium carbonate (Li:TM=1.2:0.8) and magnesium oxide (TM:Mg=1.00:0.02) powders are mixed evenly by dry mixing, and then kept at 870°C for 15 hours to obtain a magnesium-doped modified positive electrode material with a particle size of about 200 nm; the magnesium-doped modified positive electrode material is further mixed evenly with In(NO3)3 (TM:In=1.00:0.03) by wet mixing, heated and stirred until it becomes a paste, and then dried, followed by grinding and keeping at 600°C in an air atmosphere for 5 hours to obtain a micro-nano-sized magnesium-doped indium-coated lithium-rich manganese-based positive electrode material with a particle size of about 200 nm. The micro-nano-sized magnesium-doped indium-coated lithium-rich manganese-based positive electrode material is assembled into a 2032 half-cell for testing. Figure 3 As shown, the gram capacity retention rate is 94.8% after 500 cycles at 1C rate.

[0064] Example 4

[0065] (1) First, MnSO4·H2O, NiSO4·6H2O and CoSO4·7H2O were dissolved in deionized water at a molar ratio of Mn:Ni:Co=3:2:1 to prepare a transition metal salt solution with a concentration of 1.0 mol / L. Then, the precipitant sodium carbonate and the complexing agent ammonium sulfate were dissolved in deionized water to prepare a precipitant-complexing agent mixed solution with a sodium carbonate concentration of 2.0 mol / L and an ammonium sulfate concentration of 0.8 mol / L. Finally, 200 mL of deionized water was added to the reactor and kept warm to 50°C. Nitrogen was pre-flowed as a protective gas, and then the transition metal salt solution and the precipitant-complexing agent mixed solution were simultaneously pumped into the coprecipitation reactor. The stirring speed was set to 500 rpm and the pH value was controlled at 11.3. After the liquid was added, the mother liquor was aged for 24 hours, then filtered, washed and dried at 120°C for 24 hours to obtain the precursor Mn 3 / 6 Ni 2 / 6 Co 1 / 6 (OH)2 powder.

[0066] (2) The precursor prepared in step (1) and lithium carbonate (Li:TM=1.2:0.8) and magnesium oxide (TM:Mg=1.00:0.01) powders were mixed evenly by dry mixing, and then kept at 850°C for 15 hours to obtain a magnesium-doped modified positive electrode material with a particle size of about 200 nm; the magnesium-doped modified positive electrode material was further mixed evenly with InCl3 (TM:In=1.00:0.005) by wet mixing, heated and stirred until it became a paste, and then dried, and then ground and kept at 600°C in an air atmosphere for 5 hours to obtain a micro-nano-sized magnesium-doped indium-coated lithium-rich manganese-based positive electrode material with a particle size of about 200 nm. The micro-nano-sized magnesium-doped indium-coated lithium-rich manganese-based positive electrode material was assembled into a 2032 half-cell for testing, and the first cycle discharge capacity was 275.3 mAh / g, and the first efficiency was 86.56%.

[0067] Example 5

[0068] (1) First, Mn(NO3)2, Ni(NO3)2 and Co(NO3)2 were dissolved in deionized water at a molar ratio of Mn:Ni:Co=4:1:1 to prepare a transition metal salt solution with a concentration of 2.0 mol / L. Then, the precipitant NaOH and the complexing agent NH3·H2O were dissolved in deionized water to prepare a precipitant-complexing agent mixed solution with a NaOH concentration of 2.0 mol / L and an NH3·H2O concentration of 0.4 mol / L. Finally, 200 mL of deionized water was added to the reactor and kept warm to 40°C. Argon was pre-passed as a protective gas, and then the transition metal salt solution and the precipitant-complexing agent mixed solution were simultaneously pumped into the coprecipitation reactor. The stirring speed was set to 1500 rpm and the pH value was controlled at 11.8. After the liquid was added, the mother liquor was aged for 24 hours, then filtered, washed and dried at 120°C for 24 hours to obtain the precursor Mn4 / 6 Ni 1 / 6 Co 1 / 6 (OH)2 powder.

[0069] (2) The precursor prepared in step (1) and lithium carbonate (Li:TM=1.14:0.8) and magnesium oxide (TM:Mg=1.00:0.01) powders were mixed evenly by dry mixing, and then kept at 850°C for 15 hours to obtain a magnesium-doped modified positive electrode material with a particle size of about 200 nm; the magnesium-doped modified positive electrode material was further mixed evenly with In(NO3)3 (TM:In=1.00:0.02) by wet mixing, heated and stirred until it became a paste, and then dried, and then ground and kept at 600°C in an air atmosphere for 5 hours to obtain a micro-nano-sized magnesium-doped indium-coated lithium-rich manganese-based positive electrode material with a particle size of about 200 nm. The micro-nano-sized magnesium-doped indium-coated lithium-rich manganese-based positive electrode material was assembled into a 2032 half-cell for testing, and the first cycle discharge capacity was 278.2 mAh / g, and the first efficiency was 85.6%.

[0070] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the embodiments. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. The obvious changes or modifications derived from them are still within the protection scope of the invention.

Claims

1. A method for preparing a micro-nano size magnesium-doped indium-coated lithium-rich manganese-based positive electrode material, characterized in that: The following steps are involved: Under an inert atmosphere, a transition metal salt solution, a precipitant solution and a complexing agent solution are added to a reaction kettle containing a bottom solution. After the addition is completed, the obtained mother solution is aged for more than 0 hours, filtered, washed and dried to obtain a lithium-rich manganese-based positive electrode material precursor; the transition metal salt includes a manganese salt; The lithium-rich manganese-based positive electrode material precursor, lithium salt and magnesium source are uniformly mixed and sintered to obtain a bulk magnesium-doped lithium-rich manganese-based positive electrode material; Then the obtained bulk magnesium-doped lithium-rich manganese-based positive electrode material is evenly mixed with an indium source, and heated and kept warm in an oxygen-containing atmosphere to obtain a micro-nano-sized magnesium-doped indium-coated lithium-rich manganese-based positive electrode material.

2. The preparation method according to claim 1, characterized in that: The transition metal salt further comprises one or a combination of two of a nickel salt and a cobalt salt; The manganese salt is a combination of one or more of manganese nitrate, manganese sulfate and manganese acetate; The nickel salt is a combination of one or more of nickel nitrate, nickel sulfate and nickel acetate; The cobalt salt is a combination of one or more of cobalt nitrate, cobalt sulfate and cobalt acetate; In the transition metal salt solution, the total concentration of the transition metal salt is 0.5-4M, and the molar ratio of manganese, nickel and cobalt is x:y:z, 1 / 3≤x<1, 0≤y≤1 / 2, 0≤z≤1 / 2; The precipitant is a combination of one or more of sodium hydroxide, sodium bicarbonate, sodium carbonate, and oxalic acid, and the concentration of the precipitant solution is 0.5-10M; The complexing agent is a combination of one or more of ammonia water, ammonium sulfate and ammonium chloride, and the concentration of the complexing agent solution is 0.1-5M.

3. The preparation method according to claim 1, characterized in that: The inert atmosphere is one or a combination of nitrogen and argon; The precipitant solution and the complexing agent solution are introduced separately or in combination; During the liquid feeding process, the pH value of the solution system in the reactor is maintained at 10.3-12.0, the temperature in the reactor is maintained at 20-80° C., and the stirring speed in the reactor is maintained at 500-2000 r / min; The aging time is greater than 0 and less than or equal to 48 hours; The base liquid is a combination of one or more of deionized water and complexing agent solution, and the pH value of the base liquid is 10.3-12.

0.

4. The preparation method according to claim 1, characterized in that: The chemical formula of the lithium-rich manganese-based positive electrode material precursor is Mn x Ni y Co z (OH)2, 1 / 3≤x<1, 0≤y≤1 / 2, 0≤z≤1 / 2; The average particle size of the lithium-rich manganese-based positive electrode material precursor is 100nm-1μm; The morphology of the lithium-rich manganese-based positive electrode material precursor is flaky primary particles.

5. The preparation method according to claim 1, characterized in that: The lithium salt is a mixture of one or more of lithium hydroxide, lithium nitrate, lithium carbonate, lithium oxalate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium bis(oxalatoborate); The magnesium source is a mixture of one or more of magnesium nitrate, magnesium oxide, magnesium sulfate, magnesium citrate, magnesium chloride, and magnesium lactate; The ratio of the molar amount of lithium in the lithium salt to the total molar amount of transition metal in the lithium-rich manganese-based positive electrode material precursor is 1.12:0.8-1.25:0.8; The molar amount of magnesium in the magnesium source is 0.01%-5% of the total molar amount of transition metals in the lithium-rich manganese-based positive electrode material precursor.

6. The preparation method according to claim 1, characterized in that: The sintering temperature is 800-900° C., and the sintering time is 10-24 hours.

7. The preparation method according to claim 1, characterized in that: The indium source is one of indium nitrate and indium chloride or a mixture of the two; The molar amount of indium in the indium source is 0.01%-5% of the total molar amount of transition metal in the lithium-rich manganese-based positive electrode material precursor; The bulk magnesium-doped lithium-rich manganese-based positive electrode material and the indium source are uniformly mixed in a manner of dry mixing or wet mixing, or both.

8. The preparation method according to claim 1, characterized in that: The oxygen-containing atmosphere is one or both of oxygen and air; The heating and heat preservation temperature is 300-700°C, and the heating and heat preservation time is 30min-6h.

9. The micro-nano size magnesium-doped indium-coated lithium-rich manganese-based positive electrode material prepared by the preparation method according to claim 1.

Citation Information

Patent Citations

  • Preparation of concentration gradient magnesium-doped lithium-rich manganese-based oxide positive electrode material and lithium battery application of concentration gradient magnesium-doped lithium-rich manganese-based oxide positive electrode material

    CN113299902A

  • Submicron small-particle-size lithium-rich manganese-based precursor as well as preparation method and application thereof

    CN118255402A

  • Surface modification method of lithium-rich layered oxide positive electrode material

    CN118335959A

  • Ternary lithium battery positive electrode material precursor and preparation method thereof, ternary lithium battery positive electrode material and preparation method and application thereof

    CN111029561A